Socioeconomic and Lifestyle Assessment of Selected Forest Based Communities in Omo Biosphere Reserve, Ogun State, Nigeria - T.A. Oladele; M.K.C. Sridhar; A.O. Raji (Journal of Applied Sciences and Environmental Management, 2020)
This study assessed socio-economic characteristics and lifestyle of selected forest based communities in Omo Biosphere Reserve, Ogun state in  southwest Nigeria. The study aim was to explore the influence of socioeconomic factors on their lifestyle, quality of life and implications for forest  environment. A sample of 180 respondents from three enclaves was selected using simple random sampling. Data collected was analyzed using SPSS version 20 and presented as Tables and charts. The results showed that 86.11 per cent of them were adults between ages 31years and 70years who have families, responsibilities to cater for and have capacity to further expand their land into the forest. Only 2.2 per cent of the respondents  have no formal education indicating a great decline in illiteracy. About 75.56 per cent have incomes ranging between 500,000 to 1,000,000 yearly. 58 per cent respondents have a household size ranging between 6-10 persons. 7.22 per cent have farm size less than 3 Ha while the rest have more up to 10 Ha. 83 per cent of the respondents were involved in cocoa farming while the remaining 17 per cent shared kola, palm and plantain crops  farming. The type of constraints affecting the livelihood strategy often influences the mitigation measures undertaken by farmers in the study area. On health, malaria is the most prevalent disease experienced by 73.3 per cent respondents. However, the health care facilities are far from residents and also inadequate. As a result, about 95.6 per cent resorted to self-medication using herbs in case of illness. Younger and active age groups have their resultant socio-economic implications for forest environment but the obvious is its negativities in respect of exploiting more lands for farming hence, government should ensure increase awareness aimed at protecting the forest in order to prevent further forest encroachers.